2014
DOI: 10.1088/0957-0233/25/2/025602
|View full text |Cite
|
Sign up to set email alerts
|

Measuring strain and stress distributions along rebar embedded in concrete using time-of-flight neutron diffraction

Abstract: In modern society, architectural and civil engineering structures such as reinforced concrete buildings require high seismic performance to minimize the ‘megarisk’ exposed from urban earthquake hazards. In the reinforced concrete structures, the bond resistance between rebar and concrete is one important parameter for discussing its performance and it has been typically evaluated by measuring the strain distribution along the embedded rebar. Here, we present in-situ strain and stress measurements for the rebar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…Lengths of the anchorage region can be predicted to be about 85 mm for σ ap =125 MPa and about 145 mm for σ ap =248.5 MPa, and the average bond stresses are calculated to be about 6.4 MPa and 5.9 MPa, respectively. These values are different from rough estimation in our previous study [7], but more reliable since the bond stress distribution obtained here assists to determine these values accurately. On the other hand, several peaks can be found in the bond stress distribution with about 20 mm in intervals.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Lengths of the anchorage region can be predicted to be about 85 mm for σ ap =125 MPa and about 145 mm for σ ap =248.5 MPa, and the average bond stresses are calculated to be about 6.4 MPa and 5.9 MPa, respectively. These values are different from rough estimation in our previous study [7], but more reliable since the bond stress distribution obtained here assists to determine these values accurately. On the other hand, several peaks can be found in the bond stress distribution with about 20 mm in intervals.…”
Section: Introductioncontrasting
confidence: 99%
“…3), and we demonstrated that the neutron diffraction technique can be a novel strain measurement method for rebar embedded in concrete [5,6]. More recently, threedimensional deformation behavior of the embedded rebar including the axial and transverse strains was successfully measured under pull-out loading using Time-of-Flight (TOF) neutron diffraction with the engineering diffractometer, TAKUMI in MLF (Materials and life Science Experimental Facility) of J-PARC (Japan Proton Accelerator Research Complex) [7]. Furthermore, it was demonstrated by some application studies using TAKUMI that the neutron diffraction technique is available to assess the bond deterioration due to rebar corrosion and crack generation in concrete [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations